Interaction of Aβ1–42 peptide or their variant with model membrane of different composition probed by infrared nanospectroscopy. Issue 3 (2nd January 2018) - Henry, S.; Bercu, N. B.; Bobo, C.; Cullin, C.; Molinari, M.; Lecomte, S.
Abstract : Toxicity of Aβ peptides involved in Alzheimer's disease is linked to the interaction of intermediate species with membranes. Abstract : Toxicity of Aβ peptides involved in Alzheimer's disease is linked to the interaction of intermediate species with membranes. Nanoscale Infrared Spectroscopy enhances the study of the morphology and the secondary structure of the peptides as fibers or oligomers interacting with membranes of different compositions, with nanometer scale resolution. Membrane models are used to investigate the role of different lipids in their interactions with Aβ peptides. This work clearly brings to light that the presence of cholesterol in membranes is favorable to the interaction with Aβ peptides in oligomers or aggregates.